Prevelence of adverse childhood experiences in foster and redintial care population - Alves, Mafalda Coelho Pinto (2023)
ABSTRACT: Childhood adversity is associated with adverse outcomes, including mental health issues, among other challenges. Children in out-of-home care, particularly in Residential and Foster Care, face a heightened risk of Adverse Childhood Experiences. Nonetheless, research has not thoroughly examined the prevalence of ACEs in this vulnerable population. This systematic review aims to fill this gap by identifying ACE prevalence among children and youth in these care settings. It involved a thorough search across 32 electronic databases, resulting in 18 relevant studies. The findings suggest that these children experience a high prevalence of ACEs, with Neglect, Emotional Abuse, and Physical Abuse being the most common. Moreover, these prevalence rates surpass those found in the general community, highlighting the unique challenges these children encounter. In addition, children in Foster Care appear to have higher risk of Sexual Abuse than the Residential Care population. Tailored interventions and prevention strategies are urgently needed to address these traumatic experiences and improve the well-being of these vulnerable children. Further research, especially within diverse cultural contexts is encouraged.